Nilai Tambah VCO Pada Unit Bisnis Agroindustri “Andana” di Kabupaten Lombok Utara - Tajidan Tajidan; Halil Halil; Efendy Efendy; FX Edy Fernandez (Universitas Mataram, 2019)
Community service aims to improve understanding and application of financial management in the